EKRANISASI NOVEL SUNSHINE BECOMES YOU KARYA ILANA TAN KE FILM SUNSHINE BECOMES YOU KARYA SUTRADARA ROCKY SORAYA - Suwella, Titi Fitri; Nurizzati, Nurizzati; Zulfadhli, Zulfadhli (Universitas Negeri Padang, 2018)
This study aims to: (a) describe the episode of Ilana Tan's novel Sunshine Becomes You; (b) describe the movie episode of Sunshine Becomes You by director Rocky Soraya; (c) describe the episode of Ilana Tan's novel Sunshine Becomes You novel with Sunshine Becomes You directed by Rocky Soraya. This research type is qualitative research with descriptive method. This research data is the episode of novelty novel Sunshine Becomes You by Ilana Tan and Sunshine Becomes You film directed by Rocky Soraya. Data collection techniques have three stages. First, read Ilana Tan's Sunshine Becomes You novel, and then follow Sunshine Becomes You directed by Rocky Soraya. Second, the data collection phase of the novel episode of Sunshine Becomes You by Ilana Tan and Sunshine Becomes You film by director Rocky Soraya were collected through recording and observation techniques. Third, the stage of inventorying data into data inventory format. The research findings are episodes of 30 novel episodes, while in the film there are 26 episodes. In the film there are 5 additional episodes, and a reduction of 9 episodes, while the episode of a novel story that changes varies after being turned into a movie, found 15 episodes. It happens because of the creativity of the director while adapting the novel to the movie.Keywords : novel, movie, ekranisasi, episode